The major histocompatibility complex of reindeer - Olsaker, I.; Røed, K. H. (Rangifer, 1990)
The major histocompatibility complex (MHC) is a system of closely linked genes showing an extremely high degree of polymorphism. These genes are major elements in the government of specific immune reactions. Consequently they may represent a genetic marker system well suited to investigate variability in selective pressure from disease agents on different populations. On this background we have started investigation of the MHC complex in reindeer (Rangifer tarandus L). The MHC complex consist of polymorphic regions as well as regions conserved during evolution which should allow the use of cross-species reagents. We have shown that human MHC gene probes hybridize with genomic DNA from reindeer, and thus can be used as a tool in reindeer MHC research. By RFLP (restriction fragment length polymorphism) analysis using these probes we have also been able to show polymorphism in MHC related genes from reindeer.